Review of the Fund Disbursement Process at the Public Service Agency of the Politechnic of State Finance STAN (Case Study of Teaching Honorarium Payment in 2023) - Adhitama, Satria; Uliansyah, Beta Andri Anggiano; Bartholdi, Bayu Augustee; Yhoganjaya, Yhoganjaya (Jurnal Manajemen Pelayanan Publik, 2025)
The implementation of training at the Politechnic of State Finance STAN (PKN STAN) has led to administrative issues, particularly in the form of delayed honorarium payments to trainers. This delay not only affected the financial situation of the trainers but also had the potential to lower motivation and reduce the quality of teaching. This study aims to explore the process of disbursing funds to the public service agency at the Politechnic of State Finance STAN (PKN STAN), specifically regarding the payment of honorariums in the 2023 budget year. A qualitative approach was used, with data collected through in-depth interviews with individuals directly involved in the honorarium disbursement process. The results revealed that the delay in payments was caused by limited human resources in the Service and Business Development Unit, which handles business services. The increased number of trainings was not matched by adequate staff, leading to delays in processing administrative documents. Additionally, the business process burdened a single officer with all stages of training, causing an imbalance in workload and further delays. The study recommends adding more staff and improving the business process by separating tasks before and after training to enhance the efficiency of honorarium disbursement.